Linking service quality, value, and loyalty in the V-o-D service context through a review of literature - Satyaki Datta; Tathagata Ghosh (Cogent Business & Management, 2022)
Video-on-demand (V-o-D) service is quickly establishing its presence in the online entertainment sector. Therefore, it becomes imperative to understand the parameters used by consumers to evaluate V-o-D service quality. Though the service literature has an ample of studies discussing the service quality of various service sector, and their corresponding effects on consumer behaviour, little is known about the dimensions of V-o-D service quality. We address this gap by conducting a robust review of literature to identify the prospective parameters attributing to V-o-D service quality and propose their influence on various dimensions of consumer value such as functional, social, emotional, epistemic, and conditional. Thereafter, the effect of value on loyalty dimensions such as conative and action is examined. These inter-construct relationships explored and identified through the literature review are validated through interview of a small sample of V-o-D consumers.
Keywords: 650; entertainment service; loyalty; service quality; value; video-on-demand